A dialética rotina escolar-saúde: fatores que contribuem para o adoecimento docente - Melo, Leandro Ferreira De [UNIFESP] (2020)
Teaching has been the subject of study in different areas of knowledge, such as education and health. One of the spheres that has been extensively explored is the quality of teaching life, mainly due to the numerous problems related to their physical-emotional destabilization. This research aimed to identify and understand which factors interfered in the school routine and, consequently, in teaching health. We sought to assess the relationship between school routine and the triggering of symptoms related to Burnout Syndrome, as well as self-efficacy, use of alcohol and tobacco in teachers of Kindergarten, Elementary, High School and University Education. It was hypothesized that the school routine is affected not only by factors intrinsic to it, but also by external factors. The methodological procedures for data collection were carried out through questionnaires validated in Brazil and made available on the SurveyMonkey platform. The sample consisted of a number of 3,077 educators from all over Brazil who were invited to participate in the research through media and social networks. To assess the relationships and intensities between the variables Burnout, school routine, selfefficacy, use of alcohol and tobacco in teachers of Basic and University Education, mathematical models, called "networks", were created from the data collected. The analyzes showed that the school routine has been a mechanism that contributes to the onset of psychosomatic symptoms in teaching health. Research has shown that these symptoms are directly related to Burnout Syndrome, such as depression, anxiety, alcohol and tobacco use. It was also clear that it is not the school routine per se that affects teaching health and effectiveness, as there are extra-school precedents that dialectically affect the school routine. It is mentioned, the lack of “effective” policies for valuing the teaching profession (teaching career), as well as, preventive policies for their health. It is no wonder that there has also been a growing lack of credibility in the teaching career by the government, the media, students and the family. These factors directly contributed to the emotional destabilization and consequently the teaching illness. In addition to these findings, there are countless others. Thus, it is necessary to plan and implement political investment actions, especially in the area of valuing and preventing careers and teaching health.